The problems of viewing performance epistemology and other minds - Bennett, Michael Y. 1980- (Routledge advances in theatre and performance studies., 2021)
"The Problems of Viewing Performance challenges long-held assumptions by considering the ways in which knowledge is received by more than a single audience member, and breaks new ground by, counterintuitively, claiming that viewing performance is not a shared experience. Given that viewers come to each performance with differing amounts and types of knowledge, they each make different assumptions as to how the performance will unfold. Often modified by other viewers and often after the performance event, knowledge of performance is made more accurate by superimposing the experiences and justified beliefs of multiple viewers. These differences in the viewing experience make knowledge surrounding a performance intersubjective. Ultimately, this book explains the how and the why audience members have different viewing experiences. The Problems of Viewing Performance is important reading for theatre and performance students, scholars and practitioners, as it unpacks the dynamics of spectatorship and explores how audiences work"